Anime & manga digital coloring guide : choose the colors that bring your drawings to life! - Sakurai, Teruko; Akariko (Tokyo Tuttle Publishing, an imprint of Periplus Editions (HK) Ltd, 2023)
"A colour science expert's must-have colouring guide for manga and anime artists! Author Teruko Sakurai, Japan's leading colourist, applies her expert knowledge of colour to drawing effective anime and manga. Starting with the basics, Sakurai shares her secrets on how to provide your characters and scenes with the right colours to accurately express their moods and actions. This all-in-one guide allows you to become a skilled colourist in just a few easy lessons. Here are just some of the key topics presented in this all-in-one handbook: How to select the right hair and eye colors to express the personality and mood of a character; The basics of coloru theory and how to match the colour palette of a scene with the story being told; Colour's role in conveying emotion - and the essential colours used to capture a particular mood; Hundreds of palette colour combinations and swatches with CMYK and RGB percentages-- all at your fingertips. This book shows you how to become a skilled digital colourist just by following a few simple guidelines--and how to refine your illustrations further using professional-level digital shading and coloration techniques. With hundreds of tips and sample palettes to refer to, Anime & Manga Digital Colouring Guide is a book every manga and anime artist will want to have!"--Publisher's description.
Color basics : for people who draw -- Eye and hair colors that create a character's image : color pyschology for coloring characters (part one) -- The new science of color : for people who draw -- How colors communicate emotions : color psychology for coloring characters (part two) -- World views created through color : practice catalog.
"With 1000 color combinations"--Cover.
Translation of: Kyara No Miryoku Wo Saidaigen Ni Hikidasu! Manga Kyara Haishoku No Kyoukasho.
Keywords: Color drawing. -- Technique; Computer art -- Technique; Instructional and educational works; Manga (Comic books) -- Technique